Shallow slow earthquakes to decipher future catastrophic earthquakes in the Guerrero seismic gap - R. Plata-Martinez (Nature Portfolio, 2021)
New offshore observations in the Guerrero seismic gap discovered shallow slow earthquakes, which suggest that a portion of the plate interface undergoes stable slip. This may explain the long return period of large earthquakes and why have previous large earthquakes not propagated into the gap.